(untitled) (American Journal of Islam and Society, 2014)
In the aftermath of the Arab Spring, some advocated a turn toward “tradition,” thereby raising fears that women would be pushed out of the public arena despite their active participation and would even lose those gains made under previous governments. The debates around gender parity vs. complementarity that were stirred up were not new, but they did manage to acquire new cogency in the context of the emotionally charged deconstruction of the old political system and the subsequent transition to new governments. The arguments made by both sides were often couched within a framework of liberal human rights or in terms of Islamic tradition. Gender and Equality in Muslim Family Law is a valuable contribution to the discussion on the apparent contradiction between these discourses and a learned attempt to bridge them. The editors of this collective book, which stems from a number of workshops organized by the Oslo Coalition on Freedom of Religion or Belief, explore how gender equality, as shaped by contemporary ideas of human rights, can be reconciled with the Islamic legal tradition, which is rooted in pre-modern conceptions of justice. In the first chapter, Mir-Hosseini examines the classical fiqhī understanding of gender justice by focusing on qiwāmah (guardianship of women), which is enshrined in most Muslim family codes, and overviews twentieth-century reforms and codifications. She also discusses the ideas of al-Tahir al-Haddad (d. 1935) and Fazlur Rahman (d. 1988), two reformists who influenced subsequent discourses on equality in the family within an Islamic framework. Her contribution ends with a looks at the emergence of political Islam, transnational feminism, and non-governmental organizations (NGOs), all of which add a new dimension to preexisting debates. The rest of the book is divided into two sections. The first explores some concrete efforts at legal reform and social activism that reconcile Islam and human rights. Mulki al-Sharmani delves into the concept of qiwāmah in Egyptian law and in courtroom practice, pointing out the legal strategies pursued by litigants and the disconnect between the model of marriage upheld by family codes and the actual practice of marriage. Marwa Sharafedin analyzes Egyptian women’s rights NGOs and their discourse on personal status law that blend, to varying degrees, religious and human rights frames ...